Tetracycline-Tet Repressor Binding Specificity: Insights from Experiments and Simulations - Aleksandrov, Alexey (The Biophysical Society, 2009)
Tetracycline (Tc) antibiotics have been put to new uses in the construction of artificial gene regulation systems, where they bind to the Tet repressor protein (TetR) and modulate its affinity for DNA. Many Tc variants have been produced, both to overcome bacterial resistance and to achieve a broad range of binding strengths. To better understand TetR-Tc binding, we investigate a library of 16 tetracyclines, using fluorescence experiments and molecular dynamics free energy simulations (MDFE). The relative TetR binding free energies are computed by reversibly transforming one Tc variant into another during the simulation, with no adjustable parameters. The chemical variations involve polar and nonpolar substitutions along one entire edge of the elongated Tc structure, which provides many of the protein-ligand contacts. The binding constants span five orders of magnitude. The simulations reproduce the experimental binding free energies, when available, within the uncertainty of either method (±0.5 kcal/mol), and reveal many additional details. Contributions of individual Tc substituents are evaluated, along with their additivity and transferability among different positions on the Tc scaffold; differences between D- and B-class repressors are quantified. With increasing computer power, the MDFE approach provides an attractive complement to experiment and should play an increasing role in the understanding and engineering of protein-ligand recognition.